How are the vision, mission, and values disclosed on the websites of large companies? - Carvalho, João M. S. (2022)
It is important that companies disclose their vision, mission, and values in their websites, in order to seek to have a positive impact on the behaviour and attitudes of stakeholders. We analysed a sample of 120 websites of the largest companies in the 40 most developed countries in the world. We conclude that most companies, explicitly or implicitly, continue to use these management and strategic planning tools. However, many of them will not be making the best use of such instruments. Theoretical and practical implications are drawn from this study.